2016
DOI: 10.1063/1.4943356
|View full text |Cite
|
Sign up to set email alerts
|

The unique effect of in-plane anisotropic strain in the magnetization control by electric field

Abstract: The electric field control of magnetization in both (100)- and (011)-Pr0.7Sr0.3MnO3/Pb(Mg1/3Nb2/3)0.7Ti0.3O3(PSMO/PMN-PT) heterostructures were investigated. It was found that the in-plane isotropic strain induced by electric field only slightly reduces the magnetization at low temperature in (100)-PSMO/PMN-PT film. On the other hand, for (011)-PSMO/PMN-PT film, the in-plane anisotropic strain results in in-plane anisotropic, nonvolatile change of magnetization at low-temperature. The magnetization, remanence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Recently, 2–2-type heteroepitaxial ME composite thin films have been extensively investigated due to their high ferroelectric and ferromagnetic properties, low leakage current, high quality interface between the ferroic phases, and control of the crystallographic orientation of each layer. The strain-mediated direct ME coupling, implying magnetic field-induced piezoelectric potential, has been observed in various heteroepitaxial composites, including ferromagnetic La 1– x Sr x MnO 3 and ferroelectric oxides. ,, However, the lattice misfit strain along with the strong clamping effect from the substrate degrades both piezomagnetic and piezoelectric coefficients resulting in reduced strain-mediated ME coupling. Similarly, the strain-mediated converse ME effect, electric field-induced magnetic moment change, has been negligible in thin epitaxial ME composites, and interface charge-mediated ME coupling has mainly contributed toward modulating the magnetic moment of the ferromagnetic layer. On the other hand, avoiding the substrate clamping effect between ferroic phases significantly enhanced the strain-mediated converse ME coupling in epitaxial ferromagnetic films grown on ferroelectric single-crystalline substrates. Therefore, relaxation of the substrate clamping effect or development of nonstrain-mediated coupling dynamics are required for further improvement of the ME response of heteroepitaxial composites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, 2–2-type heteroepitaxial ME composite thin films have been extensively investigated due to their high ferroelectric and ferromagnetic properties, low leakage current, high quality interface between the ferroic phases, and control of the crystallographic orientation of each layer. The strain-mediated direct ME coupling, implying magnetic field-induced piezoelectric potential, has been observed in various heteroepitaxial composites, including ferromagnetic La 1– x Sr x MnO 3 and ferroelectric oxides. ,, However, the lattice misfit strain along with the strong clamping effect from the substrate degrades both piezomagnetic and piezoelectric coefficients resulting in reduced strain-mediated ME coupling. Similarly, the strain-mediated converse ME effect, electric field-induced magnetic moment change, has been negligible in thin epitaxial ME composites, and interface charge-mediated ME coupling has mainly contributed toward modulating the magnetic moment of the ferromagnetic layer. On the other hand, avoiding the substrate clamping effect between ferroic phases significantly enhanced the strain-mediated converse ME coupling in epitaxial ferromagnetic films grown on ferroelectric single-crystalline substrates. Therefore, relaxation of the substrate clamping effect or development of nonstrain-mediated coupling dynamics are required for further improvement of the ME response of heteroepitaxial composites.…”
mentioning
confidence: 99%
“…The initial magnetic properties of the LSMO films were found to degrade following PZT deposition. In prior reports, it has been shown that the modulation of the magnetic properties in an epitaxial ME composite results from interface charge-mediated converse ME coupling and strain-mediated ME coupling across the ferroelectric/ferromagnetic interface. In the case of interface charge-mediated converse ME coupling, the interfacial magnetization is changed due to electrostatic charge accumulation at the PZT/LSMO interface from ferroelectric spontaneous polarization. , Prior studies have shown that interfacial charge accumulation modulates the valence state of Mn from the high spin state Mn 3+ (S = 2) to the low spin state Mn 4+ (S = 3/2) near the interface. This results in an interfacial ferromagnetic to antiferromagnetic phase transition in the accumulation state and, thereby, changes the magnetic moment of LSMO.…”
mentioning
confidence: 99%